Publicly Accessible Library Services to Business in the USA and Australia: A Comparison and Analysis. Issue 4 (1st October 2020) - Bachmann, Brendan
ABSTRACT: There are various models of library services to business, but these are relatively underutilised in an Australian setting. They are however far better developed in the USA, where there is a long and successful history of providing small businesses with a variety of support services through publicly accessible libraries. This paper defines and explores the models of business services in libraries, reflecting on examples of these models in practice from both Australia and the USA. It then considers the future opportunities for developing and enhancing library service for business provision in Australia, based on these insights.